Supporting Awareness in Creative Group Work by Exposing Design Rationale - Farooq, Umer; Carroll, John (Human Technology, 2011)
When creativity is taken as a long-term, complex, and collaborative activity, support for awareness is required for group members to monitor the development of ideas, track how these ideas became narrowed, and understand how alternatives are being implemented and integrated by colleagues. In this paper, we investigate the effects of exposing design rationale to convey awareness, specifically activity awareness, in group creativity. Through evaluating a prototype, we investigate status updates that convey design rationale, and to what consequences, in small groups in fully distributed collaboration. We found that status updates are used for a variety of purposes and that participants' comments on their collaborators' status updates provided feedback. Overall, results suggest that participants' awareness about their collaborators' future plans increased over time. Majority of participants found the status updates useful, particularly those with higher metacognitive knowledge. Based on our results, two design strategies for activity awareness are proposed.